Differences In Interleukin-6 and Liver Enzyme Level Based On Clinical Severity of COVID-19 Patients at Dr. M. Djamil General Hospital, Padang - Elsesmita, Elsesmita; Medison, Irvan; Herman, Deddy (Indonesian Society of Respirology (ISR), 2025)
Background: COVID-19 pathogenesis involves the release of proinflammatory cytokines and chemokines, known as a